2021
DOI: 10.3390/s21227693
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Current Integration of Multiple Personalised Wearable Sensors for Environment and Health Monitoring

Abstract: The ever-growing development of sensor technology brings new opportunities to investigate impacts of the outdoor environment on human health at the individual level. However, there is limited literature on the use of multiple personalized sensors in urban environments. This review paper focuses on examining how multiple personalized sensors have been integrated to enhance the monitoring of co-exposures and health effects in the city. Following PRISMA guidelines, two reviewers screened 4898 studies from Scopus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…52 While measuring personal environmental exposure accuracy is crucial, understanding its impact on human health should go further than the data collection and mitigate the effects of exposures like pollution. 53 There appears to be a gap in the literature as data collection is often the end goal without any corresponding action. To progress the proliferation and scalability of wearables and to successfully improve health, it appears necessary to encourage the joint monitoring and assessment of physiological, psychological and environmental exposure to ensure comprehensive and accurate comprehension of health.…”
Section: Monitoring Environment Exposurementioning
confidence: 99%
“…52 While measuring personal environmental exposure accuracy is crucial, understanding its impact on human health should go further than the data collection and mitigate the effects of exposures like pollution. 53 There appears to be a gap in the literature as data collection is often the end goal without any corresponding action. To progress the proliferation and scalability of wearables and to successfully improve health, it appears necessary to encourage the joint monitoring and assessment of physiological, psychological and environmental exposure to ensure comprehensive and accurate comprehension of health.…”
Section: Monitoring Environment Exposurementioning
confidence: 99%
“…While this is very appealing, the ability to create such a multiple sensor system is extremely challenging, since it requires constant communication and integration of information across modalities. Zhang et al , 273 who studied wearable sensors, identified several key obstacles to integrating multiple sensors: choosing the right sensor for each purpose, determining how many sensors are needed and their specific functionalities, and the intelligent and effective combination and processing of different data. This requires critical decision-making in terms of costs, recruitment, implementation, and data validity.…”
Section: Charting a Course For The Future Of Implantable Sensors In M...mentioning
confidence: 99%
“…This requires critical decision-making in terms of costs, recruitment, implementation, and data validity. 273,274 …”
Section: Charting a Course For The Future Of Implantable Sensors In M...mentioning
confidence: 99%
“…Improving pedestrian comfort and safety involves an understanding of the complexity of the walking experience. In outdoor environments, stress may be due to a variety of environmental factors, such as crowdedness, lighting, visibility, proximity to motor vehicles, and facility design, among others [1] [2]. Measuring the stress that pedestrians experience during their travels can serve as valuable information towards improving the mobility experience and, in particular, mitigating pedestrian safety given the alarming number of pedestrian casualties caused by conflicts with motor vehicles.…”
Section: Introductionmentioning
confidence: 99%